Answer:
32°, 58°
Step-by-step explanation:
Let one acute angle measure x.
The other acute angle measures 2x - 6.
The sum of the measures of the acute angles of a right triangle is 90.
x + 2x - 6 = 90
3x - 6 = 90
3x = 96
x = 32
2x - 6 = 2(32) - 6 = 58
Answer: 32°, 58°
B -13 -34i
(7 + 2i)(-3 - 4i)
Take the 7 then times it buy the second bracket 7x(-3-4i) then take 2i from the first bracket and times it with the second bracket 2ix (-3-4i)
Then keep simplifying
Answer:
3. x = 53
4. x = 60
Step-by-step explanation:
Answer:
-3
Step-by-step explanation:
The statement is,
→ Sum of 9 and -16 increased by 4
The equation will be,
→ {9 +(-16)} + 4
→ (9 - 16) + 4
→ -7 + 4
→ [ -3 ]
Hence, the solution is -3.
<span>Let the height of tree be denoted as AB and the shadow cast by the tree be BE. ABE is the triangle formed the tree, rays and the ground. Let the height of the person be CD and the length of his shadow be DE. CDE is the triangle formed by the person, rays and the ground.
We have two triangles. Both the person and the tree stand vertically over the horizontal ground, therefore they make 90 degrees with the ground. The angle formed at the ground is the same for the both the triangles. Therefore, by AA similarity the two triangles are similar.
We know that if two triangles are similar, then their sides are proportional.
Therefore,
AB/CD =BE/DE
AB/6 = 143/11
AB= (143/11) *6
AB = 78 ft.</span>